A history of gold mining in the Asante region of Ghana (1950-1972) - David Damtar (2021)
This doctoral research project addresses the significant lacunae in the inadequate inclusive understanding of Ghana’s gold mining history over the late colonial and early post-colonial period that encompass multiple socio-political actors in the industry’s encounters with state and society. The thesis examines the overarching contestations among multiple social and political actors over access to the potential benefits to be derived from mineral extraction within this changing socio-political landscape. It utilises a wide range of archival materials encompassing colonial and post-colonial state and mining companies’ records, combined with in-depth oral histories with diverse mining communities’ actors with lived experiences of these settings, dating to the mid-to-late twentieth century.